ROLE OF BPHTB ON ORIGINAL LOCAL GOVERNMENT REVENUE THROUGH MEASUREMENT OF EFFECTIVENESS AND CONTRIBUTION IN SIDOARJO REGENCY - Galih Wicaksono; Nurul Ainif; Sovie Arrachelyta Rizky Nur Habibah (Institute of Computer Science (IOCS), 2022)
The Customs for the Acquisition of Land and or Building Rights (BPHTB) is one type of local tax whose revenue potential can be increased through a series of appropriate strategies. This study aims to determine how the role of BPHTB on Regional Original Income (PAD) in Sidoarjo Regency, through its effectiveness and contribution to PAD. This research is a quantitative descriptive, by calculating the ratio of effectiveness and contribution of BPHTB to PAD, 2018-2020. Using secondary data sourced from research journals and the realization of regional income in Sidoarjo Regency. The findings of this study are that the target and realization of BPHTB are fluctuating, while PAD always increases every year. Effectiveness is in the very effective category, while the contribution to PAD is in the not enough category.